Engineering geological investigation of Gololcha dam for evaluation of leakage and abutment slope stability, Eastern Ethiopia - Sishaw Merdassa; Tola Garo; Yadeta C. Chemeda; Shankar Karuppannan; Mahlet Tesfaye (Scientific African, 2024)
The Ethiopian economy is primarily dependent on agriculture, making the construction of water harvesting facilities, such as dams, crucial for improving the productivity of this sector. The ongoing construction of the Gololcha dam on the Kurkura River located in Eastern Ethiopia aims to enhance irrigation schemes in the region. However, the dam site's complex geological and structural conditions pose challenges related to leakage and slope instability. Hence, this study focuses on addressing the abutment slope stability and leakage condition of this dam. This study employed kinematic analysis and the Limit Equilibrium Method (LEM) to assess slope stability. Additionally, engineering geological mapping, discontinuity surveys, seismic refraction tomography (SRT), and in-situ permeability testing were used to evaluate the leakage condition of the dam site. Notably, the permeability and SRT survey results identified potential leakage zones to the depth of 35, 30, and 35 m at the left, right, and central foundations of the dam, respectively. The kinematic method revealed one planar and two wedge modes of failure in the slope section covered by slightly weathered and fractured basalt rock at the right abutment. Further stability analysis of these two modes of failures via LEM analysis indicated slope instability under saturated conditions, emphasizing the role of pore water pressure. Furthermore, LEM modeling was directly utilized using the Slide 6.0 software to analyze the slope stability condition of the left abutment of the dam. This modeling also uncovered instability under saturated conditions. Based on the study findings, this study recommended curtain grouting to address potential leakage, as well as slope flattening and removing unstable rock wedges and loose material to stabilize unstable slope sections.